THE ROLE OF GREEN TEA IN ORAL HEALTH – A REVIEW - Mohan, Meenakshi; Jeevanandan, Ganesh; Raja S, Mithun (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Tea is the most widely consumed and a popular beverage in the world. Over the past decade, molecular components of teas and their health benefits on humans have received increasing attention from researchers. Functional foods are foods with positive health benefits that extend beyond their normal nutritional value. They interrupt the functions of the body and help in the management of specific health conditions and preventing pathologic changes. One such nature's gift is green tea. Green tea, a leading beverage in the Far East for the past thousand years, is an important source of polyphenol antioxidants. (EGCG) epigallocatechin 3 gallate, a polyphenol, constitute the most interesting components in green tea leaves. There is an increasing interest on the health benefits of green tea in the field of oral health. Green tea is renowned for its antioxidant, anti-cariogenic, anti inflammatory and antimicrobial properties. This traditional beverage is also used in the management of chronic systemic diseases including carcinoma. Recent studies has emphasized that in addition to the microbial activity, the host immuno-inflammatory reactions destroy the oral tissues to a greater extent. In such cases green tea is considered to be a natural preventive and curative agent. There is a growing search of evidence for understanding the beneficial role of green tea and its polyphenols in oral health. Numerous studies have shown the beneficial effects on the regular intake of green tea in maintaining oral health. Even though studies demonstrate the health effects of green tea polyphenols, more clinical and biological studies to support guidelines for green tea intake as part of prevention and treatment of specific oral pathologies are needed.